Motivation of Gen Z to use The Strava Application as A Way to Maintain Fitness in Rembang Regency - Hanif Ardana Heidianto; Dwi Gansar Santi Wijayanti (Journal of Physical Education Health and Sport, 2025)
This study aims to determine the motivation of Gen Z towards using the STRAVA application as a way to maintain fitness in Rembang district. The method used in this research is descriptive quantitative research method. In this study, 60 people who are Gen Z were taken as research samples. The results of the minimum score of 20, the maximum score of 80, the average score of 54.59, and the standard deviation of 11.880. The distribution of motivation levels shows that most respondents are in the high category, as many as 29 respondents (47.5%). In addition, 7 respondents (11.5%) had very high motivation, while 24 respondents (39.3%) were in the low category, and only 1 respondent (1.6%) had very low motivation. From these results, it is known that the majority of Gen Z in Rembang Regency have strong motivation in maintaining fitness by utilizing the STRAVA application to support their physical activities. In other words, the activity tracking feature, social interaction in the STRAVA community, and personal goals in maintaining a healthy body are additional motivational drives for Gen Z. Thus, Gen Z motivation tends to be high in using the STRAVA application as a way to maintain physical fitness in Rembang Regency.